Owning the Rubric : student engagement in rubric design and use : final report. - Northcote, Maria; Williams, Anthony; Christian, Bev; Jackson, Wendy; Joseph, Sue; Kilgour, Andrew; Kilgour, Peter; Morton, Jason; Rickett, Carolyn; Seddon, John (Australia. Dept of Education and Training (DET), 2019)
The project focuses on collaboratively constructing and using assessment resources designed in partnership between teachers and students in higher education contexts. Traditionally, the early stages of assessment design were the domain of teachers. In recent years, many educators and researchers have called for increased levels of involvement by students during the development of assessment criteria, instructions and rubrics. By engaging students to work collaboratively with their university teachers to prepare and create assessment guidelines and rubrics, there is a greater potential for students to take ownership of and be accountable for their own learning outcomes. The aim of the project was to investigate the innovative and collaborative use of assessment rubrics, in partnership between students and academic staff, in order to develop a model of collaborative rubric practice that is applicable in higher education contexts. The context of the project was important as it was conducted across six cohorts of undergraduate students and their university teachers from five different disciplines in three higher education institutions. The varied contexts provided a range of settings, each of which represented multiple cases to explore across multiple sites. A mixture of different degree year levels was also represented. The project approach adopted a four-phase design across a two-year period. Employment of the project's methodology began in Phase 1 with team organisation, establishing project boundaries, scope and aims, and the construction of data gathering instruments required for Phase 2. Phase 2 employed the Delphi technique to establish the characteristics of effective rubric design, informed by a comprehensive literature review and advice provided by members of an expert panel. The outcome of Phase 2 was an instrument, the Effective Rubric Characteristics Inventory (ERCI) that guided the subsequent rubric co-construction processes followed by six cohorts. Also during Phase 2, a multiple case-study approach was adopted in which six cohorts of students at three institutions worked with their lecturers to co-construct a rubric that they would use in the following or same semester. The lecturers and students in each cohort were guided by a protocol including the ERCI and a set of recommendations for practice to enact when co-constructing assessment rubrics. In Phase 3, the six cohorts of students and their lecturers at three institutions used their co-constructed projects, guided by another set of protocols of practice. Data about the lecturers' and students' perceptions of these processes were gathered during Phases 2 and 3. Finally, in Phase 4, a model for rubric co-construction and use was designed. The Model for Collaborative Rubric Construction and Use is housed in the project's website which will be disseminated through workshops for members of the Australian higher education sector. [Executive summary, ed]